Factors Affecting Intensity Whistleblowing of Employees on The Potential Fraud of The National Health Insurance Program (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2019)
The National Health Insurance Program (Jaminan Kesehatan Nasional /JKN) is an effort by the Government to fulfillment of the basic needs of public health. However, this program is also susceptible to fraud. Hospital as the Secondary Level Reference Facility that collaborates with the Social Security Agency (Badan Penyelenggara Jaminan Sosial/ BPJS) should establish a fraud prevention system in the JKN implementation. Employees’ positions are at the forefront to reveal various forms of fraudulence including those related to JKN by means of whistleblowing. The ‘Planned Behavior Theory’ analyzes the attitude, subjective norms and behavior control perception factors that affect the intention of JKN-claim related employees' to whistleblow. The purpose of this study was to determine and analyze the influence of attitudinal factors, subjective norms and perceptions of behavioral control on the intention of employee whistleblowing behavior on JKN fraud programs in Hospital X Central Java Province This study is a mixed-method study with a ‘sequential explanatory design’ approach. The study was started by using a quantitative method and then continued by means of qualitative method in order to produce a hopefully more complete study result. The results of the study prove attitudes (p-value 0.038), subjective norms (p-value 0.040) and perceptions of behavioral control (p-value 0.005) jointly influence the intention of employee whistleblowing. From the results of the OR it can be seen the order of the three independent variables that have the largest to the smallest influence on employee whistleblowing intentions, namely perceptions of behavior control, attitudes and subjective norms. This can be a reference to the management priority scale to make efforts to increase the intention of employee whistleblowing in Hospital X and is expected to be able to change the